Hierarchical genetic structure shaped by topography in a narrow-endemic montane grasshopper - Noguerales, Víctor (BMC Evol Biol, 2016)
BACKGROUND: Understanding the underlying processes shaping spatial patterns of genetic structure in free-ranging organisms is a central topic in evolutionary biology. Here, we aim to disentangle the relative importance of neutral (i.e. genetic drift) and local adaptation (i.e. ecological divergence) processes in the evolution of spatial genetic structure of the Morales grasshopper (Chorthippus saulcyi moralesi), a narrow-endemic taxon restricted to the Central Pyrenees. More specifically, we analysed range-wide patterns of genetic structure and tested whether they were shaped by geography (isolation-by-distance, IBD), topographic complexity and present and past habitat suitability models (isolation-by-resistance, IBR), and environmental dissimilarity (isolation-by-environment, IBE). RESULTS: Different clustering analyses revealed a deep genetic structure that was best explained by IBR based on topographic complexity. Our analyses did not reveal a significant role of IBE, a fact that may be due to low environmental variation among populations and/or consequence of other ecological factors not considered in this study are involved in local adaptation processes. IBR scenarios informed by current and past climate distribution models did not show either a significant impact on genetic differentiation after controlling for the effects of topographic complexity, which may indicate that they are not capturing well microhabitat structure in the present or the genetic signal left by dispersal routes defined by habitat corridors in the past. CONCLUSIONS: Overall, these results indicate that spatial patterns of genetic variation in our study system are primarily explained by neutral divergence and migration-drift equilibrium due to limited dispersal across abrupt reliefs, whereas environmental variation or spatial heterogeneity in habitat suitability associated with the complex topography of the region had no significant effect on genetic discontinuities after controlling for geography. Our study highlights the importance of considering a comprehensive suite of potential isolating mechanisms and analytical approaches in order to get robust inferences on the processes promoting genetic divergence of natural populations. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12862-016-0663-7) contains supplementary material, which is available to authorized users.